2019
DOI: 10.46912/jbrcp.105
|View full text |Cite
|
Sign up to set email alerts
|

Post-traumatic Stress Disorder and Functional Disability among Internally Displaced Persons in North-East Nigeria

Abstract: The prolonged Boko Haram crises in North-East Nigeria caused serious displacement and left the survivors with multiple psychological consequences such as Posttraumatic stress disorder (PTSD). A high prevalence rate of PTSD among Internally Displaced Persons (IDPs) has been reported across literatures. This study aimed to determine the factors that are associated with PTSD and its relationship with functional disability among IDPs in Yobe State, Nigeria. This was a cross sectional study of 450 respondents, recr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…In this review, a study conducted in Sudan, South Darfur, at the Darfur Campaign study site, showed the lowest prevalence of PTSD (14.9%) [ 35 ], while a study conducted in IDP camps in Yobe State in northeastern Nigeria showed the highest prevalence of PTSD (94.2%) [ 2 ]. Three studies were from Ethiopia [ 20 , 26 , 33 ]; five studies were from Nigeria [ 2 , 24 , 38 40 ] and the remaining studies were from Kenya [ 34 ], Somalia [ 10 ], Sudan [ 35 ], South Sudan [ 36 ], Uganda [ 21 ] and the Democratic Republic of Congo (DRC) [ 37 ]. The included studies were categorized as having a low risk of bias (quality score 6 to 8).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this review, a study conducted in Sudan, South Darfur, at the Darfur Campaign study site, showed the lowest prevalence of PTSD (14.9%) [ 35 ], while a study conducted in IDP camps in Yobe State in northeastern Nigeria showed the highest prevalence of PTSD (94.2%) [ 2 ]. Three studies were from Ethiopia [ 20 , 26 , 33 ]; five studies were from Nigeria [ 2 , 24 , 38 40 ] and the remaining studies were from Kenya [ 34 ], Somalia [ 10 ], Sudan [ 35 ], South Sudan [ 36 ], Uganda [ 21 ] and the Democratic Republic of Congo (DRC) [ 37 ]. The included studies were categorized as having a low risk of bias (quality score 6 to 8).…”
Section: Resultsmentioning
confidence: 99%
“…By design, all included studies were cross-sectional. This study included a total of 7,590 participants [2,10,20,21,24,26,[33][34][35][36][37][38][39][40]. The included articles were published between 2008-2023.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…However a study of communities in Jos South Local Government area [53] reported opioids as displacing nicotine and cannabis out of the first three most used substances. Variations in types of substances and pattern of use from place to place has been documented [54] in a previous research work and depends on location, availability and age range considered. However the UNODC drug survey in Nigeria found cannabis as the most used substance nationwide [2].…”
Section: Discussionmentioning
confidence: 75%
“…A sixty-seven percent (67%) prevalence rate for the current use of CCCS was reported for both long-distance truck drivers (Dada et al, 2021) and a community study of 600 participants aged between 15 and 73 years. (Nwoga et al, 2019). Opioid pain medication was the most commonly used substance among hospital patients for non-medical reasons (Fela-Thomas et al, 2020).…”
Section: The Prevalence Rate For Non-medical Use Of Tramadol Codeine ...mentioning
confidence: 99%
“…and Monkey Tail -produced by mixing Ogogoro (a local gin) with the seeds, roots and leaves of cannabis and leaving it to ferment for some days -were also commonly reported among young adults (Dumbili et al, 2020;Uthman et al, 2016). Less common substance abuse included inhaling faeces from a septic tank, refuse gas, or laundry blue, and smoking dried lizard faeces, dried paw and cassava leaves (Diwe et al, 2017;Isah et al, 2018;Nwoga et al, 2019;Okechukwu, 2013). The leaves are dried, ground into a powdery form and smoked.…”
Section: New Psychoactive Substances (Nps)mentioning
confidence: 99%